2017
DOI: 10.1136/bmjgh-2016-000235
|View full text |Cite
|
Sign up to set email alerts
|

Limited understanding, limited services, limited resources: patients’ experiences with managing hypertension and diabetes in Cambodia

Abstract: IntroductionHealth system responses to the emergence of non-communicable diseases (NCDs) in many Southeast Asian nations, Cambodia included, have been insufficient. Little is known about how people suffering from such conditions behave in constrained contexts. We examined the experience of patients with NCDs as they seek care for their conditions and manage them.MethodsIn-depth interviews with 28 purposively selected patients with hypertension and/or diabetes using an interview guide to capture the trajectory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Major investments and reforms have improved maternal health services, 57 58 more so than other services. 59 This has likely had an influence on the community's trust in the services, with implications for the private sector. The private sector dominates non-maternal health service uptake, and remains mostly unregulated and unintegrated with the public sector.…”
Section: One Right Choicementioning
confidence: 99%
“…Major investments and reforms have improved maternal health services, 57 58 more so than other services. 59 This has likely had an influence on the community's trust in the services, with implications for the private sector. The private sector dominates non-maternal health service uptake, and remains mostly unregulated and unintegrated with the public sector.…”
Section: One Right Choicementioning
confidence: 99%
“…However, due to limited drug stocks at public health facilities these patients tend to be provided with drug prescriptions to purchase such medicines. For example, a recently published study on hypertension and diabetes found that patients first sought medical treatment with modern allopathic medicine, and in most cases, medicines were purchased elsewhere [35]. To limit the influence of this potential confounding factor, chronic disease was used as a control variable.…”
Section: Limitationsmentioning
confidence: 99%
“…The findings from Nepal and Cambodia 7 bring to the fore the challenges of effectively designing and implementing policies to provide free medicines at point of care overcoming systemic and financial bottlenecks to their sustainability. In both cases medicines are in theory free at point of care, but in practice, population access is poor.…”
mentioning
confidence: 99%
“…The case of Cambodia also underlines the importance of and the struggles around access to medicines for lifelong chronic conditions such as diabetes and hypertension in countries that are rapidly moving through the epidemiological transition while still facing a substantial burden of communicable diseases and maternal and child mortality. Jacobs et al 7 point that the public health system in Cambodia has been developed along the principles of a district model geared towards fighting communicable diseases. Health centres are not prepared or equipped to deliver appropriate long-term care for patients living with diabetes and hypertension, enabling the private sector to fill the void.…”
mentioning
confidence: 99%
See 1 more Smart Citation